Molecular and morphological characterization of haemosporidian parasites in Bornean plantain squirrels - Harttini, Neeni. (Universiti Malaysia Sarawak (UNIMAS), 2012)
Previous studies have shown that small mammals are natural hosta to two genera of haemosporidian parasites, Hepatocystis and Plasmodium. In Peninsular Malaysia, 2 Hepatocystis spp. and 3 Plasmodium spp. have been described in small mammals. Early description and classification of these parasites was solely based on morphology of infected RBCs, life history traits and species of host infected. These conventional ways to identify and classify these haemosporidian parasites had obscured the evolutionary relationship and mislead terminology of malaria parasites. When DNA technology improved and molecular data became available in the 20th century, Hepatocystis spp. was described in flying foxes from peninsular Malaysia and another study done in sarawak revealed that fruit bats and flying foxes were infected with Hepatocystic spp.